ANALISIS PENGARUH PERSONALISASI PENGALAMAN PENGGUNA (USER EXPERIENCE) TERHADAP LOYALITAS PELANGGAN DI E-COMMERCE. - DANDA, DANDA BAGASKORO; Daniati, Erna Daniati (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
This study analyzes the influence of user experience (UX) personalization on customer loyalty in e-commerce through a literature review. A total of 25 journal articles published between 2015 and 2024 were reviewed to identify the role of personalized product recommendations, adaptive interfaces, and relevant content in shaping customer behavior. The synthesis reveals that personalization enhances satisfaction, which subsequently fosters loyalty outcomes such as retention, repurchase intention, and positive word-of-mouth. This study contributes a conceptual model for future empirical validation and provides practical insights for e-commerce practitioners to develop data-driven personalization strategies while maintaining user trust.